Strigolactone and Karrikin Signaling Influence the Recruitment of Wild Tobacco’s Root Microbiome in the Desert - Jie Cheng; Shuai Luo; Gundega Baldwin; Xu Cheng; Ian T. Baldwin; Suhua Li (Agronomy)
Survival in desert ecosystems poses significant challenges for plants due to harsh conditions. Plant microbiomes are thought to promote resilience; however, whether plant hormones, specifically strigolactones (SLs) and karrikins (KARs), shape plant microbiomes remains unknown. The recruitment of root-associated microbiomes in Nicotiana attenuata, a model desert plant, silenced in specific genes associated with SL biosynthesis (CCD7) and perception (D14), karrikin perception (KAI2), and in the shared receptor (MAX2), required for both pathways, was studied. SL and KAR signaling, with MAX2 as a co-regulator, fine-tuned the assembly of root-associated microbiomes, with unique and shared regulatory functions on bacterial microbiome recruitment, particularly in taproot. Significant variation among the different plant genotypes in bacterial diversity and composition in taproot and lateral roots provides a foundation for future research to explore how microbiomes function in plant resilience in these harsh environments.